Dihydromyricetin Ameliorates Inflammation-Induced Insulin Resistance via Phospholipase C-CaMKK-AMPK Signal Pathway. (5th October 2021) - Hou, Lianjie; Jiang, Fangyi; Huang, Bo; Zheng, Weijie; Jiang, Yufei; Cai, Gengyuan; Liu, Dewu; Hu, Ching Yuan; Wang, Chong
Abstract : Patients with metabolic syndrome have a higher risk of type II diabetes and cardiovascular disease. The metabolic syndrome has become an urgent public health problem. Insulin resistance is the common pathophysiological basis of metabolic syndrome. The higher incidence of insulin resistance in obese groups is due to increased levels of inflammatory factors during obesity. Therefore, developing a therapeutic strategy for insulin resistance has great significance for the treatment of the metabolic syndrome. Dihydromyricetin, as a bioactive polyphenol, has been used for anti-inflammatory, antitumor, and improving insulin sensitivity. However, the target of DHM and molecular mechanism of DHM for preventing inflammation-induced insulin resistance is still unclear. In this study, we first confirmed the role of dihydromyricetin in inflammation-induced insulin resistance in vivo and in vitro. Then, we demonstrated that dihydromyricetin resisted inflammation-induced insulin resistance by activating Ca 2+ -CaMKK-AMPK using signal pathway blockers, Ca 2+ probes, and immunofluorescence. Finally, we clarified that dihydromyricetin activated Ca 2+ -CaMKK-AMPK signaling pathway by interacting with the phospholipase C (PLC), its target protein, using drug affinity responsive target stability (DARTS) assay. Our results not only demonstrated that dihydromyricetin resisted inflammation-induced insulin resistance via the PLC-CaMKK-AMPK signal pathway but also discovered that the target protein of dihydromyricetin is the PLC. Our results provided experimental data for the development of dihydromyricetin as a functional food and new therapeutic strategies for treating or preventing PLC.